CLINICAL AND PSYCHOPATHOLOGICAL FEATURES OF INTERNALLY DISPLACED WOMEN WITH ADJUSTMENT DISORDERS - Isakov, R.I.; Skrypnikov, A.M.; Herasymenko, L.O.; Hryn, K.V.; Kydon, P.V.; Vdovina, O.O. (World of Medicine and Biology, 2020)
Vast numbers of internally displaced persons and the threatening growth rate of emigration create the need to pay increased attention to various aspects of psychopathological conditions that arise in response to changes in habitual living conditions. In addition to clinical consequences, the prevalence is accompanied by significant negative social and economic consequences both for society as a whole and for the patient himself, significantly deteriorating his quality of life and level of social functioning. There are significant gender differences in crisis response, in particular, women are the most vulnerable in the vast majority of stressful situations. We carried out a comprehensive clinical, psychopathological and psychodiagnostic examination of 48 internally displaced persons with the established adjustment disorder (F43.2) with studying and careful analysis of anamnestic data using a special questionnaire. The study found that the leading clinical manifestations of internally displaced women are the presence of anxiety and depression in the structure of adjustment disorders, social disintegration and the presence of psychosocial maladjustment. Clinical differences of internally displaced women with adjustment disorders affect the quality of life, change the system of social support and values, contribute to the reduction of productive activities in everyday life.